Utilization of Postnatal Care Services Among Women in Alkufa City - Doaa Mahmood Naji; Lamia Dhia Al Deen (Genius Journals, 2022)
Postnatal care is important component of maternal health care services to improve outcomes associated with pregnancy, childbirth and complication after birth also to provide women with important information on how to care for themselves and their children, counselling on maternal nutrition, birth spacing and immunization.
Keywords: Antenatal; Postnatal care; Primary health care; period